2020
DOI: 10.1136/bmjopen-2019-036138
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of dual versus triple antithrombotic therapy (DAT vs TAT) in patients with atrial fibrillation following a PCI: a systematic review and network meta-analysis

Abstract: ObjectiveCreating an appropriate antithrombotic therapy for patients with atrial fibrillation (AF) who have undergone percutaneous coronary intervention (PCI) remains a dilemma. Several clinical trials compared the use of a dual antithrombotic therapy (DAT) regimen with a direct oral anticoagulants including (apixaban, dabigatran, edoxaban or rivaroxaban) and a P2Y12 inhibitor versus a triple antithrombotic therapy (TAT) that includes a vitamin K antagonist plus aspirin and a P2Y12 inhibitor in patients with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…1 ). 12 , 13 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 All meta-analyses except for one Cochrane review 26 were ranked as having low or critically low quality levels according to the AMSTAR 2 criteria ( Supplemental Table S1 ). The high-quality Cochrane review compared DOACs to VKAs post-PCI, which was not a focus for this review.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). 12 , 13 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 All meta-analyses except for one Cochrane review 26 were ranked as having low or critically low quality levels according to the AMSTAR 2 criteria ( Supplemental Table S1 ). The high-quality Cochrane review compared DOACs to VKAs post-PCI, which was not a focus for this review.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in our meta -analysis, results from studies using various types of DOACs were pooled together on the assumption that all DOACs are comparable in terms of safety and efficacy. However, this may not be true as demonstrated by Altoukhi et al [21] study which ranked the different types of DOACs as per their efficacy and safety. In Ruiz et al, out of the 145 patients who received concomitant antiplatelet therapy, 79 percent of them used ASA whereas 21 percent of them were given P2Y12 inhibitor, hence the results of this study do not solely reflect the safety and efficacy of ASA alone but rather the antiplatelet therapy in general.…”
Section: Discussionmentioning
confidence: 97%
“…Head-to-head comparisons are not available regarding different DOACs in cases of AF patients undergoing PCI. A recently published NMA found that as part of the DAT apixaban was ranked first as the preferred therapy in terms of major or clinically relevant non-major bleeding and stroke, rivaroxaban ranked first as the preferred therapy in terms of MI and stent thrombosis, while dabigatran ranked first as the preferred therapy in terms of all-cause mortality ( 36 ). Various DOACs may have different risk-benefit profiles in combination strategies ensuring implementation of an optimal individualized antithrombotic regimen for patients receiving long-term OAC and undergoing PCI ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%